2019
DOI: 10.1177/0021998319859924
|View full text |Cite
|
Sign up to set email alerts
|

Design of the ultrahigh molecular weight polyethylene composites with multiple nanoparticles: An artificial intelligence approach

Abstract: This study proposes a suitable composite material for acetabular cup replacements in hip joint that involves ultrahigh molecular weight polyethylene, a clinically proven material, as the matrix. To design new ultrahigh molecular weight polyethylene composites with multiple reinforcements for the improvement in mechanical and tribological performance, artificial neural network and genetic algorithm, the two artificial intelligence techniques, are employed. Published reports on the use of ultrahigh molecular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…For example, Shams et al employed AI methods to estimate and optimize the silver nanoparticle concentration on the treated silk fabrics for antimicrobial properties (Shams Nateri et al, 2019). Vinoth and Datta used the artificial neural network and genetic algorithm to design a novel nanoparticle reinforced polymer composite for replacements in hip joints (Vinoth and Datta, 2020). Mahmoud et al implemented the artificial neural network to simulate and predict the removal efficiency of several organic contaminates from aqueous systems using iron nanoparticle sorbents (Mahmoud et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Shams et al employed AI methods to estimate and optimize the silver nanoparticle concentration on the treated silk fabrics for antimicrobial properties (Shams Nateri et al, 2019). Vinoth and Datta used the artificial neural network and genetic algorithm to design a novel nanoparticle reinforced polymer composite for replacements in hip joints (Vinoth and Datta, 2020). Mahmoud et al implemented the artificial neural network to simulate and predict the removal efficiency of several organic contaminates from aqueous systems using iron nanoparticle sorbents (Mahmoud et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…With R 2 values for training and testing above 0.8 as well as mean absolute errors not exceeding 4.1%, it was thus shown that sliding speed and load determined the wear losses more significantly than the particle types and fractions. Recently, Vinoth and Datta [53] also used 153 experimental data sets from literature to predict mechanical properties of UHMWPE composites with multi-walled carbon nanotubes (MWCNT) and graphene reinforcements in dependency of seven input variables comprising composite composition, particle size, and mechanical bulk properties. A feed forward ANN with scaled conjugate gradient back propagation, hyperbolic tangent transfer functions and 3 (for Young's modulus) or 5 (for the ultimate tensile strength) hidden layers were utilized, achieving correlation coefficients for the outputs of 0.93 and 0.97, respectively.…”
Section: Thermoplastic Matrix Compositesmentioning
confidence: 99%
“…A few studies, however, manage to extract real insights and thus additional knowledge from a large and broad database. The comprehensive works in the field of composite materials from Kurt and Oduncuoglu [52], Vinoth and Datta [53], and Hasan et al [63,64] utilizing literature-extracted databases may be highlighted here and can serve as excellent examples. The current showstopper is still the availability of sufficient and comparable datasets as well as the handling of uncertainties regarding test conditions and deviations.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…In addition, various researchers have applied ML and AI approaches to predict and optimize the tribological behavior of different materials and operating conditions with manifold applications in mind [14][15][16][17][18][19][20]. For instance, Alambeigi et al [21] investigated the accuracy of predictive AI models by comparing them with experimental results obtained by testing the dry sliding contact of sintered steels [21].…”
Section: Design Of Materials Compositionmentioning
confidence: 99%